2021
DOI: 10.1590/0102-672020210002e1640
|View full text |Cite
|
Sign up to set email alerts
|

Cistoadenoma Seroso De Pâncreas. Por Que a Acurácia É Baixa Aos Exames De Imagem?

Abstract: RESUMO - RACIONAL: Apesar da recomendação atual que o cistoadenoma seroso deva ser tratado de forma conservadora, significativa parte dos pacientes com essa condição ainda é operada por dúvida diagnóstica. OBJETIVO: Analisar causas da baixa acurácia diagnóstica do cistoadenoma seroso. MÉTODOS: Estudo retrospectivo de portadores de cistoadenoma seroso de um banco de dados de dois ambulatórios de cirurgia hepatopancreaticobiliar entre 2006 e 2020. Foram incluídos pacientes com lesões típicas de cistoadenoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Due to its atypical morphology, especially concerning unilocular and macrocystic SCN, it has been frequently misdiagnosed as other cystic lesions. In 27 cases studied by Amico et al, 10 patients underwent surgery based on suspicion of MCN (seven cases), IPMN (two cases) and cancer (one case) [ 50 ].…”
Section: Scnmentioning
confidence: 99%
“…Due to its atypical morphology, especially concerning unilocular and macrocystic SCN, it has been frequently misdiagnosed as other cystic lesions. In 27 cases studied by Amico et al, 10 patients underwent surgery based on suspicion of MCN (seven cases), IPMN (two cases) and cancer (one case) [ 50 ].…”
Section: Scnmentioning
confidence: 99%
“…Walter de Biase SILVA-NETO 1 , Claudemiro QUIRESE 1 , Eduardo Guimarães Horneaux de MOURA 2 , Fabricio Ferreira COELHO 3 , Paulo HERMAN 3 ABSTRACT -Background: The treatment of choice for patients with schistosomiasis with previous episode of varices is bleeding esophagogastric devascularization and splenectomy (EGDS) in association with postoperative endoscopic therapy. However, studies have shown varices recurrence especially after long-term follow-up.…”
Section: A Queda Da Pressão Portal Após Desvascularização Esofagogást...mentioning
confidence: 99%
“…CT, magnetic resonance imaging (MRI) and magnetic resonance cholangiopancreatography, positron emission tomography (PET), and PET superseded by fused imaging with CT (PET/CT) are the radiological modalities more frequently used to image pancreatic cysts 1,24 . Once pancreatic lesions are detected on CT or MRI, endoscopic ultrasound (EUS) can also be used for further characterization, as it is a valuable tool for showing internal structures such as septa and mural nodules 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The atypical morphological presentations of serous cystadenoma of the pancreas may be the main cause for surgical indication in these patients 4,5 . MRI can be a helpful adjunct for discrimination of serous cystadenoma of the pancreas from pancreatic malignancy 4 . 68 Ga-FAPI is a novel and promising PET tracer for imaging of pancreatic malignancy 6,7 .…”
mentioning
confidence: 99%
“…Despite low potential for malignancy, a significant number of patients with serous cystadenoma of the pancreas are still operated on 3. The atypical morphological presentations of serous cystadenoma of the pancreas may be the main cause for surgical indication in these patients 4,5. MRI can be a helpful adjunct for discrimination of serous cystadenoma of the pancreas from pancreatic malignancy.4 68 Ga-FAPI is a novel and promising PET tracer for imaging of pancreatic malignancy 6,7.…”
mentioning
confidence: 99%